Avaliação de produção de biogás e potencial energético na micro bacia do rio Buriti – Itaipulândia/PR - Angeli, Letieri Laerte (2015)
This study aimed to analyze the possibility of implementing a bio digester system in the pig condominium properties of micro river basin Buriti, in the municipality of Itaipulândia/PR, eliminating the odor caused by the activity as this interferes with the region’s tourism. Besides contributing to tourism the implementation brings environmental, social and financial benefits. To realize the study visits were made in the properties and industries, and interviews with owners belonging to this micro area in order to understand the processes and facilitate the technique of the harnessing the biogas generated in treating swine waste to drive cogeneration of energy systems. The end of the study if large opportunity to reduce the emission of gases in manure management systems through bio digesters, failing to cause strong odors and reducing costs for companies with inputs for boilers and furnaces.